STUDI TENTANG PENGALAMAN KERJA, KOMITMEN KERJA, DUKUNGAN ORGANISASI DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN - Samsul Arifin; Didit Darmawan (JURNAL ILMIAH EDUNOMIKA, 2021)
Organizational effectiveness is determined by the role of human resources. The quality of human resources does not only come from work ability but also comes from extra role behaviors such as work experience, organizational commitment, and perceived organizational support. Together with other variables, it is expected that all of these factors are carried out effectively in aggregate. Organizational citizenship behavior needs to be observed in order to obtain the expected work results of the organization. This study will examine work experience, organizational commitment, perceived organizational support, and its effect on employee performance. The purpose of this study was to analyze and determine the effect of work experience, organizational commitment, and perceived organizational support on employee performance. The number of samples carried out using the census technique were 72 employees. The analysis tool is multiple linear regression analysis, t test and F test assisted by SPSS 26 program. From the results of the study, it was found that work experience had a significant effect on employee performance. Organizational commitment has a significant effect on employee performance. Perception of organizational support has a significant effect on employee performance. Work experience, organizational commitment, and perceived organizational support have a significant simultaneous effect on employee performance Keywords : Work experience, organizational commitment, perceived organizational support, job performance